The critics and Hemingway, 1924-2014 : shaping an American literary icon - Mazzeno, Laurence W. (Rochester, New York : Camden House, 2015)
Hemingway burst on the literary scene in the 1920s with spare, penetrating short stories and brilliant novels. Soon he was held as a standard for modern writers. Meanwhile, he used his celebrity to create a persona like the stoic, macho heroes of his fiction. After a decline during the 1930s and 1940s, he came roaring back with The Old Man and the Sea in 1952. Two years later he received the Nobel Prize. While his popularity waxed and waned during his lifetime, Hemingway's reputation among scholars remained strong as long as traditional scholarship dominated. New approaches beginning in the 1960s brought a sea change, however, finding grave fault with his work and making him a figure ripe for vilification. Yet during this time scholarship on him continued to appear. His works still sell well, and several are staples on high-school and college syllabi. A new scholarly edition of his letters is drawing prominent attention, and there is a resurgence in scholarly attention to-and approbation for-his work. Tracing Hemingway's critical fortunes tells us something about what we value in literature and why reputations rise and fall as scholars find new ways to examine and interpret creative work. -- Amazon.com.
Introduction: "The most interesting man in the world" -- Spokesperson for the lost generation (1924-1932) -- Writing on his own terms (1932-1952) -- The critics' darling (1952-1961) -- Posthumous evaluations (1961-1969) -- Turbulence (1970-1979) -- Calm before the storm (1980-1985) -- A "sea change" in Hemingway studies (1986-1990) -- "Hemingway": site for competing theories (1991-1999) -- Old themes, new discoveries (2000-2010) -- The undisputed champ once more (2011-2014) -- Conclusion: The enduring master.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Hemingway, Ernest, -- 1899-1961 -- Appreciation; Hemingway, Ernest, -- 1899-1961 -- Influence; Hemingway, Ernest, -- 1899-1961 -- Criticism and interpretation; Hemingway, Ernest, -- 1899-1961; LITERARY CRITICISM -- American -- General; Art appreciation; Influence (Literary, artistic, etc.); Criticism, interpretation, etc; Literary criticism; Literary criticism; Critiques littéraires.